2012
DOI: 10.3866/pku.whxb201112292
|View full text |Cite
|
Sign up to set email alerts
|

Production of 5-Hydroxymethylfurfural from Inulin Catalyzed by Sulfonated Amorphous Carbon in an Ionic Liquid

Abstract: The production of 5-hydroxylmethylfurfural (HMF) from inulin over sulfonated amorphous carbon was studied in an ionic liquid, 1-butyl-3-methylimidazolium chloride ([Bmim]Cl). The effects of reaction solvent, water content, reaction temperature, reaction time, and catalyst dosage on the yield of HMF were investigated. Experimental results indicated that optimum reaction conditions required a reaction temperature of 100°C, a reaction time of 60 min, an R value of 5 (R represents the molar ratio of added water to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[5][6][7] Therefore, ILs have been widely used in catalytic processes, such as material synthesis, organic catalysis, and more recent biomass conversion. [8][9][10][11][12][13][14][15] In 2005, Ranu and Banerjee 16 first reported that the Michael addition process could be promoted efficiently in the presence of the basic IL [bmim]OH. More than 90% product yield was achieved for all active methylene compounds examined.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Therefore, ILs have been widely used in catalytic processes, such as material synthesis, organic catalysis, and more recent biomass conversion. [8][9][10][11][12][13][14][15] In 2005, Ranu and Banerjee 16 first reported that the Michael addition process could be promoted efficiently in the presence of the basic IL [bmim]OH. More than 90% product yield was achieved for all active methylene compounds examined.…”
Section: Introductionmentioning
confidence: 99%